Intervention of Listening to Al-Qur'an Murottal to Improve Concentration on College Students - Baroroh, Ema Zati; Nurfitriani, Anisa (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2024)
Concentration difficulties among students pose a significant barrier to effective learning. Observational findings suggest that some students struggle to maintain focus, as evidenced by drowsiness and disengagement during lectures. This study aimed to investigate the impact of listening to Al-Quran murottal on college students' concentration levels. Employing a one-group pretest-posttest design, data was collected using digit span tasks and interviews from three randomly selected participants. Results revealed a notable increase in average concentration scores from 6.3 to 9 post-intervention. Furthermore, interview data indicated that two-thirds of the participants perceived an improvement in their concentration abilities. Based on both quantitative and qualitative findings, this study concludes that listening to Al-Quran murottal can positively influence students' concentration. Further research with a larger sample size and a more complex design is needed to generalize these findings.